Benchmarking the quality of breast cancer care in a nationwide voluntary system: the first five-year results (2003–2007) from Germany as a proof of concept - Rezai Mahdi; Sohn Christoph; Schumacher Claudia; Brucker Sara Y; Bamberg Michael; Wallwiener Diethelm (BMC Cancer, 2008)
Abstract Background The main study objectives were: to establish a nationwide voluntary collaborative network of breast centres with independent data analysis; to define suitable quality indicators (QIs) for benchmarking the quality of breast cancer (BC) care; to demonstrate existing differences in BC care quality; and to show that BC care quality improved with benchmarking from 2003 to 2007. Methods BC centres participated voluntarily in a scientific benchmarking procedure. A generic XML-based data set was developed and used for data collection. Nine guideline-based quality targets serving as rate-based QIs were initially defined, reviewed annually and modified or expanded accordingly. QI changes over time were analysed descriptively. Results During 2003–2007, respective increases in participating breast centres and postoperatively confirmed BCs were from 59 to 220 and from 5,994 to 31,656 (> 60% of new BCs/year in Germany). Starting from 9 process QIs, 12 QIs were developed by 2007 as surrogates for long-term outcome. Results for most QIs increased. From 2003 to 2007, the most notable increases seen were for preoperative histological confirmation of diagnosis (58% (in 2003) to 88% (in 2007)), appropriate endocrine therapy in hormone receptor-positive patients (27 to 93%), appropriate radiotherapy after breast-conserving therapy (20 to 79%) and appropriate radiotherapy after mastectomy (8 to 65%). Conclusion Nationwide external benchmarking of BC care is feasible and successful. The benchmarking system described allows both comparisons among participating institutions as well as the tracking of changes in average quality of care over time for the network as a whole. Marked QI increases indicate improved quality of BC care.